Rola dorosłych w obliczu stresu dziecięcego - Patrycja Curyło‑Sikora (Problemy Wczesnej Edukacji)
The article is a review and refers to two reflections. The first concerns the specificity of childhood stress in the face of its universality and contemporary challenges, the second results from the assumptions of health psychology and indicates the role of adults in the development of children in the face of stressful experiences. At the beginning, childhood stress is characterized, paying attention to its symptoms and sources. It is indicated that stress is an element of functioning present from the earliest years of human life. The next part shows its relational understanding, which served as an inspiration for considerations on the role of adults in shaping protective factors, treated in psychology as important for proper psychosocial development. The aim of the article is therefore to present the issue of childhood stress in a broader perspective – as a common phenomenon and at the same time requiring long term educational activities aimed at shaping and strengthening protective factors from the earliest years of life.